Exploring medical ethics' implementation challenges: A qualitative study - Jannat Mashayekhi; Mahboobeh Khabaz Mafinejad; Tahereh Changiz; Hamideh Moosapour; Pooneh Salari; Saharnaz Nedjat; Bagher Larijani (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Adherence to medical ethics principles by medical professionals is required to improve health-care system's quality. Recognizing medical ethics' challenges and attempting to resolve them are important in the implementation of medical ethics in practice. This study aimed to explore such challenges at Iran's medical sciences universities in 2018. MATERIALS AND METHODS: This descriptive, qualitative study utilized a conventional content analysis approach for data analysis. This study was conducted using purposeful sampling from participants with experience in teaching or practicing of medical ethics field, and by considering maximum variety of disciplines (e.g., gynecology, internal medicine, surgery, and medical ethics). The data were gathered using semi-structured interviews. The interview guide was designed based on previous research findings by two members of the research team and contained the main interview questions and participants had the opportunity to express their perspectives in detail. Participants were chosen from clinical and ethical faculty members as well as managers. The data collection process continued until the data saturation stage, beyond which no new information or concept achieved by continuing interviews. RESULTS: After interviewing 14 faculty members and managers, findings were classified into 4 themes, 9 categories, and 42 sub-categories; four main categories of medical ethics challenges are affected by cognitive, educational, practical, and structural factors, respectively. CONCLUSION: This study suggested that medical ethics' cognitive and educational challenges can alleviate using educational programs intended for improving qualitative and quantitative aspects of medical ethics teaching for medical professionals ranging from students to faculty members. Medical ethics' structural and practical challenges are within policymaking and scheduling activities dealt with through future researches by health-care system's managers and planners.